836 Clinical evaluation of cenp-b and scl-70 autoantibodies in silicosis patients. (24th April 2018) - Lee, S; Hayashi, H; Kumagai-Takei, N; Matsuzaki, H; Yoshitome, K; Nishimura, Y; Uragami, K; Kusaka, M; Yamamoto, S; Ikeda, M; Hatayama, T; Fujimoto, W; et al.
Abstract : Introduction: Silicosis patients (SIL) suffer from respiratory disorders and dysregulation of autoimmunity. Frequent complications such as rheumatoid arthritis, systemic sclerosis (SSc) and vasculitis are known in SIL. Furthermore, we reported previously that some SIL exhibited better respiratory conditions in association with a worse immunological status. In this study, the clinical roles of anti-CENP-B and Scl-70 autoantibodies in SIL were analysed. Methods: Plasma samples were collected from Healthy Volunteers (HV), SIL, Systemic Sclerosis (SSc). Plasma factors and autoantibodies were determined by ELISA. Statistical analysis were performed by SPSS (IBM). Results: The titer index (Log10) of anti-CENP-B autoantibody in SIL was higher than that of HV and that of SSc was higher than those of HV and SIL. This titer index was positively correlated with an assumed immune status of 1 for HV, 2 for SIL, and 3 for SSc. Moreover, although factor analysis revealed that the titer index of the anti-CENP-B autoantibody formed the same factor with the anti-Scl-70 autoantibody, IgG value and age in SIL cases, another extracted factor indicated that the IgA value and anti-Scl-70 antibody were positively related, but anti-CENP-B showed an opposite pattern in the results of the factor analysis. Conclusion: These findings indicated that the titer index of anti-CENP-B autoantibody may be a biomarker for dysregulation in SIL cases. Future clinical follow-up of SIL may therefore require both respiratory and immunological assessment